DEVELOPMENT OF PHYSICAL QUALITIES IN ATHLETICS TRAINING (Conferencea, 2022)
the owner of a healthy lifestyle (STT) physical culture needs to have knowledge – theoretical, practical skills and skills to maintain the level of readiness of his body throughout his / her lifetime at the same level.